2020
DOI: 10.1017/s1368980020003948
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of the initiative ‘Caring for the Newborn and the Mother at Home’ in Mexico

Abstract: Objective: The WHO and UNICEF recommend home visits to improve health outcomes for mothers and newborns. We evaluated the effect of home visits by community volunteers during pregnancy and postpartum on breastfeeding practices, women´s knowledge about benefits, beliefs and myths of breastfeeding, obstetric and neonatal warning signs, preparation for childbirth and initial care for newborns, and diarrhea and respiratory diseases in children. Design: Community quasi-experimental design. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
6
0
3
Order By: Relevance
“…Similar results were documented in a meta‐analysis, which found that counselling is effective at increasing rates of any breastfeeding and EB < 6mo, especially if delivered postnatally (McFadden et al, 2019). The same way, recent evidence shows that breastfeeding counselling through home visits by community health workers in rural communities in the South of Mexico improved breastfeeding practices (Unar‐Munguía et al, 2020). Also, health professionals should be trained with tools for adequate individual counselling, promotion and effective communication (Bonvecchio, Perichart, Reyes, & Rodríguez, 2018).…”
Section: Discussionmentioning
confidence: 83%
“…Similar results were documented in a meta‐analysis, which found that counselling is effective at increasing rates of any breastfeeding and EB < 6mo, especially if delivered postnatally (McFadden et al, 2019). The same way, recent evidence shows that breastfeeding counselling through home visits by community health workers in rural communities in the South of Mexico improved breastfeeding practices (Unar‐Munguía et al, 2020). Also, health professionals should be trained with tools for adequate individual counselling, promotion and effective communication (Bonvecchio, Perichart, Reyes, & Rodríguez, 2018).…”
Section: Discussionmentioning
confidence: 83%
“…In the pregnancy-puerperal cycle, actions are concentrated on mothers and are fragmented, mostly focused on breast feeding (21) . After training for the first bath, the mother, father and family will have to perform this care without assistance at home (22) . Doubts about the proper way to bathe or hold the newborn baby, the ideal water temperature and the number of baths are frequent (1,10) .…”
Section: Discussionmentioning
confidence: 99%
“…Doubts about the proper way to bathe or hold the newborn baby, the ideal water temperature and the number of baths are frequent (1,10) . Studies highlight the importance of baby care programs starting from prenatal care for better planning of the new routine and point out the impact of these actions for the prevention of neonatal mortality, especially where access to health services is limited (1,21,22) .…”
Section: Discussionmentioning
confidence: 99%
“…No ciclo grávido-puerperal as ações são concentradas nas mães e fragmentadas com foco principalmente no aleitamento materno (21) . O banho do RN é visto como um cuidado pouco debatido, é realizado treinamento no primeiro banho e depois a mãe, pai e família se depara no domicílio sozinhos para realizá-lo (22) . Dúvidas quanto a forma adequada de dar o banho ou segurar o bebê, temperatura ideal da água e quantidade de banhos são frequentes (1,10) .…”
Section: Discussionunclassified